Fluorescent Molecular Rotors for Viscosity Sensors - Lee, Seung Chul; Heo, Jeongyun; Woo, Hee Chul; Lee, Ji Ah; Seo, Young Hun; Lee, Chang Lyoul; Kim, Sehoon; Kwon, O. Pil (Chemistry - A European Journal, 2018)
Invited for the cover of this issue is the collaborative work of the groups of O-Pil Kwon (Ajou University), Chang-Lyoul Lee (Advanced Photonics Research Institute, APRI/Gwangju Institute of Science and Technology, GIST), and Sehoon Kim (Korea Institute of Science and Technology, KIST). The cover image illustrates the viscosity-sensitive fluorescent behavior of fluorescent molecular rotors (FMRs) in various viscous media. The intensity of the FMRs increases with decreasing speed of the rotor; this is portrayed as the waterwheel in the cover image. When the waterwheel slowly rotates in winter (high viscosity media), FMR—portrayed as the house in the image—shows strong fluorescent-light illumination (left-hand side of the image). In contrast, the right-hand side of image depicts decreasing fluorescence intensity with increasing rotation of the waterwheel (low viscosity media). Read the full text of the article at 10.1002/chem.201801389.